Anatomical examination of the great inguinal blood vessels in preterm and term neonates. Issue 3 (27th March 2012) - Eifinger, Frank; Lazaridis, Elpida Chochliourou; Roth, Bernhard; Koebke, Jürgen
<x xml:space="preserve">Abstract</x> It is generally accepted that vessel cannulation is technically more difficult and results in more complications in neonates. A sound anatomical knowledge of the inguinal area is therefore important in the selection of appropriately sized central line catheters as well as the approach to central vessel access. Eleven stillborns were investigated. Birth weight (mean: 2, 414 g, 900–4, 100 g) and gestational age (mean 34 1/7 weeks', 27 6/7–42 1/7) varied within normal range. The outer diameters of the femoral artery (FA), femoral vein (FV), and great saphenous vein (GSV) were determined. The distance between the anterior superior iliac spine and the pubic tubercle was set as 100% and the vessel intersection points were calculated as percentage values of the inguinal ligament length, starting at the iliac spine. The FA has a diameter of 1.9 ± 0.5 mm without correlation to gestational age. The FA crosses the inguinal ligament centrally. The FV has a diameter of 3.1 ± 1.0 mm and does have correlation to gestational age. The FV crosses the inguinal ligament at 63–64%. The GSV has a diameter of 1.4 ± 0.7 mm. Its point of intersection at the level of the inguinal ligament is 68–70%. We conclude that cannulation of the femoral artery or vein should not be performed too far (<1 cm) from the inguinal ligament. The course of the GSV is not suitable for catheter insertion. Clin. Anat. 27:376–382, 2014. © 2012 Wiley Periodicals, Inc.